TESTS OF INVISIBLE LOSSES AND CLEANING EFFICIENCY DETERMINATION IN MECHANICAL SUGAR CANE HARVESTING WITH AND WITHOUT TRASH - NEVES, JORGE LUIS MANGOLINE; MAGALHÃES, PAULO SERGIO GRAZIANO; MORAES, EDSON ESTEVES DE; ARAÚJO, FAUSTO VINICIUS DE (Revista Brasileira de Engenharia de Biossistemas, 2007)
In Brazil, the sugar cane industry processed 431.4 million tons of sugar cane during the harvestingseason 2005/2006. Nowadays, from 5 to 10% of this raw material is lost in the field when it is handor mechanically harvested respectively. Due to State law number 11.241 of 09/19/2002, after 2021burning sugar cane before harvesting will not be allowed, making it unfeasible for hand cut, thus harvesting system tend to become a 100% mechanized in feasible areas. This work quantified thein visible losses and cleaning efficiency in the cane processed by the harvester and compared the results with and without straw during the processing. The harvester, under controlled conditions, was tested at the maintenance workshop of Usina São João/Araras-SP. The tests of invisiblelosses in the harvesting system were initially conducted using clean canes (detrashed) and canes with leaves and tips. Invisible loss in the harvesting system varied from 1.2 to 2.4 %, and were larger when the cane was processed with the leaves. The cleaning efficiency of the raw material did not show significant statistical differences, but it was between 74 and 80% and in general, the loss and the cleaning efficiency were larger when using the higher rotation speed of the separatorfan (1350 rpm).